2003
DOI: 10.1016/s0735-1097(03)00829-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of aspirin on the risk of embolic events in patients with infective endocarditis

Abstract: In endocarditis patients already receiving antibiotic treatment, the addition of aspirin does not appear to reduce the risk of embolic events and is likely associated with an increased risk of bleeding. Aspirin is not indicated in the early management of patients with IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
2
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(104 citation statements)
references
References 36 publications
3
95
2
4
Order By: Relevance
“…However, in a randomized study by Chan et al [25], antiplatelet therapy was not associated with a reduced risk of embolic events when used as adjunctive therapy in combination with antibiotics. Accordingly, in our study, the ‘protective’ effect of anticoagulant therapy disappeared after the initiation of antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a randomized study by Chan et al [25], antiplatelet therapy was not associated with a reduced risk of embolic events when used as adjunctive therapy in combination with antibiotics. Accordingly, in our study, the ‘protective’ effect of anticoagulant therapy disappeared after the initiation of antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Nicolau et al [2,3] demonstrated that aspirin was effective in reducing the size of vegetations and the prevention of septic emboli in animal models of endocarditis. However, a randomized trial in humans not only failed to show a reduction in the number of clinically significant embolic events, but patients treated with aspirin had an increase in bleeding events [4]. Nevertheless, this study did not address the question of what to do in the setting of patients already on anticoagulant therapy at the time of diagnosis.…”
Section: Commentsmentioning
confidence: 88%
“…Die einzige randomisierte Studie über die Wirkung einer thrombozytenaggregationshemmenden Therapie bei Endokarditis konnte keine Risikoreduktion für das Auftreten systemischer Embolien zeigen [3]. Trotz vielversprechender experimenteller Untersuchungen sind die Ergebnisse einer antithrombotischen Therapie unter klinischen Bedingungen widersprüchlich.…”
Section: Das Risiko Einer Akuten Zerebralen Oder Systemischen Embolunclassified